From the absence in initial training to the ground floor: the difficulties faced by teachers of basic education in Caxias / MA in the applicability of law 10.639 / 2003 in the teaching of History (Research, Society and Development, 2020)
From the enactment of Law 10,639 / 2013, it became mandatory to include teaching on Afro-Brazilian and African History and Culture in Brazilian school institutions, both in elementary and high school, being a political and pedagogical framework for education of Brazil. Thus, this article seeks to reflect on the experiences of teachers of History of Basic Education, in Caxias / MA, what difficulties were faced in view of the applicability of the aforementioned law, with regard to the teaching of Afro-Brazilian and African History and Culture in the classroom. Thus, the data collected were acquired through the use of an electronic questionnaire, with the population of 20 History teachers, working in the Municipal Network of the City of Caxias / MA. In view of the collected data, we found that teachers feel difficulties to carry out a more representative insertion of issues related to Afro-Brazilian History and Culture in the classroom, given the absence in the process of initial and continuing education, in addition the school environment itself does not contribute to assist in enforcing the law, as school institutions still have a restricted view of the various possibilities of insertion to what the law adds.